‘Io nacqui Veneziano… e morrò per la grazia di Dio Italiano’. Centri e periferie nella narrativa di Ippolito Nievo - Segatori, Stefania (Incontri. Rivista europea di studi italiani, 2012)
‘I was born in Venice ... and will die Italian by God’s grace’ Centers and peripheries in Ippolito Nievo’s narrative The occasion of the 150 year anniversary of the unification of Italy and of the loss of the writer Ippolito Nievo Garibaldi (1831-1861) suggests a reading of the Nievian narrative, retracing the path advocated by Carlo Dionisotti and his investigatory method, which is without a doubt among the most innovative to be found in the last forty years of literary criticism. The application of the ‘center-periphery’, interpretative category – as expressed in a concise but effective style in the incipit of Confessioni d’un Italiano (‘Io nacqui Veneziano… e morrò per la grazia di Dio Italiano’) – has also permitted the recovery of Nievo’s lesser-known texts. Examples of these are the novel Angelo di bontà, which is set in Venice (which stands as a center of excellence in the writer’s literary-symbolic imagination) as well as stories of the Novelliere campagnuolo, in which Nievo portrays his beloved Friulian countryside. In Nievian fiction, visiting idealized places offers the reader not only stories of literary value, but also of informative value regarding civic Italy. Investigation into the function of landscape in the writer’s symbolic-narrative logic allows a grasp of the distinctive features of Italian identity occurring at the time. It is in Nievo’s masterpiece that he shows how the specific locus and the national dimension are indispensable to each other in the construction of a united fatherland.